Luminescence of CWO single crystals containing various defects - Grinyov, B.V.; Moroz, Z.T.; Nagornaya, L.L.; Pashkovsky, M.S.; Ryzhikov, V.D.; Tupitsyna, I.A.; Apanasenko, A.L. (Functional Materials, 2005)
Influence of dopant-induced defects on luminescence and performance characteristics of CWO crystals has been studied. Мо and Fe have been shown to give rise to a specific "red" emission component with decay time of several hundreds of microseconds or more, while trivalent dopants cause formation of deep charge carrier traps responsible for the millisecond range afterglow. These defects give rise also to the color centers causing absorption in the intrinsic emission band, thus deteriorating the crystal scintillation parameters. The studies performed allowed to develop a technology of large high-quality CWO crystals. The tomographic elements manufactured from those crystals showed an afterglow of less than 100 ppm after 20 ms and the light yield of about 20,000 photons per MeV. Исследовано влияние примесных дефектов на люминесцентные и функциональные характеристики кристаллов CWO. Показано, что Мо и Fe образуют в кристаллах специфические "красные" компоненты свечения с временами высвечивания несколько сотен и более микросекунд, трехвалентные примеси приводят к образованию глубоких ловушек носителей заряда, ответственных за послесвечение в миллисекундном диапазоне. Эти дефекты также ответственны за образование центров окраски, поглощающих в области собственного свечения, что ухудшает сцинтилляционные характеристики кристаллов. Проведенные нами исследования позволили разработать технологический процесс получения крупногабаритных кристаллов CWO улучшенного качества. Томографические элементы, изготовленные из этих кристаллов, имели послесвечение менее 100 ppm через 20 мс, световой выход - 20000 фотон/МэВ. Вивчено вплив домiшкових дефектiв на люмiнесцентнi i функцiональнi характеристики кристалiв CWO. Показано, що Мо i Fe утворюють в кристалах CWO специфiчнi "червонi" компоненти свiчення з часами висвiчення декiлька сотень i бiльше мiкросекунд, тривалентнi домiшки приводять до утворення глибоких пасток носiiв заряду, вiдповiдальних за пiслясвiчення у мiлiсекундному дiапазонi. Цi дефекти також вiдповiдальнi за утворення центрiв забарвлення, поглинаючих в областi власного свiчення, що погiршує сцинтиляцiйнi характеристики кристалiв. Проведенi нами дослiдження дозволили розробити технологiчний процес отримання великогабаритних кристалiв CWO полiпшеної якостi. Томографiчнi елементи, виготовленi з цих кристалiв, мали пiслясвiчення менше 100 ppm через 20 мс, свiтловий вихiд - 20000 фотон/МеВ.